The complete chloroplast genome sequence of Thymus mongolicus (Labiatae), a special spice plant - Li Huaizhu; Liang Bai; Jiqing Bai; Ping Wang; Caihua Zhou; Dou Lingling; Jiaojiao Jiang; Jun Liu; Qiaoli Wang (Mitochondrial DNA. Part B. Resources, 2020)
Thymus mongolicus is well-known spice plant and resource of traditional Chinese herbal medicine, belonging to the Thymus of the Labiatae family. In this study, the whole chloroplast genome of the T. mongolicus was sequenced, assembled and annotated, which contains 134 unique genes, including 89 protein-coding genes, 37 tRNA genes and 8 rRNA genes. A maximum likelihood phylogenetic tree based on 21 complete chloroplast genomes revealed that T. mongolicus is closely related to Mentha genus. The chloroplast genome could be used for species, varieties and medicinal materials identification, genetic engineering and Labiatae germplasm resources protection.